Studi Tegangan Tembus Minyak Transformator - Oksa Winanta, I Nyoman; Amrita, Anak Agung Ngurah; Ariastina, Wayan Gede (Jurnal SPEKTRUM, 2019)
This study aims to identify the effect of changes in temperature, water content, and electrode gap on the breakdown voltage of transformer oil. The transformer oil used in this study was Shell Diala-B and Nynas oil. Testing the effect of temperature was carried out at temperature variation of 280 C to 810 C, the effect of water content was carried out with variations ranging from 11 ppm to 31 ppm, and the effect of electrode gap was carried out in variation ranges between 1.2 mm to 2.5 mm. Breakdown voltage testing method uses hemispherical electrodes according to IEC 60156 standard of 1995. The results of the study show that the higher the temperature, the higher the breakdown voltage of transformer oil. The highest breakdown voltage in Nynas oil occurs when the temperature is 810 C which is equal to 59.27 kV. The results also show that the higher the water content, the breakdown voltage is lower. The highest breakdown voltage in Shell Diala-B oil occurs with a water content of 11 ppm which is equal to 61.35 kV. Also the greater the electrode gap, the greater the breakdown voltage. The highest breakdown voltage in Nynas oil occurs with the gap of electrode 2.5 mm which is equal to 60.02 kV.